Punishment for apostasy : conflict between the right to freedom of religion and criminal sentence, a case study in Malaysia / Mohamed Azam Mohamed Adil - Mohamed Adil, Mohamed Azam (UPENA, 2005)
My article is concerned with the conflict in laws between freedom of religion and law of apostasy within the broader Malaysian constitutional framework. The issue is controversial because, while freedom of religion is guaranteed in the Malaysian Constitution, some respective states in Malaysia have treated Muslims who intend to leave the Islamic faith as criminals. Even though there is no death penalty for apostasy in Malaysia, apostates shall be detained, fined or punishable with imprisonment up to three years. Such punishments seem contrary to the provision of Article 11(1) of the Federal Constitution which guarantees the right of freedom of religion. It also deprived individual liberty as provided in Article 5(1) of the Federal Constitution. Moreover, these punishments also seem contrary to Article 4(1) of the Federal Constitution that maintains the supremacy of the Constitution, and Article 75 that upholds the Federal law powers in the event where State law is inconsistent with the Federal law.